STUDY OF GRAIN DRYING IN THE AUTOMATED GRAIN DRYING UNIT - S. A. Pavlov; T. F. Frolova (Сельскохозяйственные машины и технологии, 2018)
Mine and column grain dryers are a fairly complex object of control in the production line. The process of grain drying is characterized  by a large number of parameters, quantitatively and qualitatively characterizing the dryer operation. First of all, this includes the criteria of maximum performance and minimum deviations of the moisture content of the dried grain from the standard values. These criteria, as studies show, are interconnected with each other: an increase in the performance П of the dryer leads to an increase in the moisture content of the grain coming out of it, and, conversely, an attempt to reduce the moisture content of grain causes the need to reduce the performance П. (Research purpose) The research purpose is to develop the expression for the transfer functions of the of grain flow control depending on perturbations of the initial moisture content and the maximum grain temperature, as well as to conduct experimental studies. (Materials and methods) The authors have developed simplified mathematical models of moisture perturbation compensation of grain coming in for drying and its heating temperature in a drying chamber by changing the dryer performance on the basis of theoretical-and-experimental studies. (Results and discussion). The authors  have obtained  expressions to control the process performance when the current humidity and temperature change through the dryer performance parameters as a function of grain moisture flow and heat used to grain heating up to an acceptable temperature. Farm tests of developed transition management functions have been implemented for dryer SZT-16 controlled by PLC S7-1200 Siemens and operating in an automatic mode. Tests have been conducted on the “Babachev” farm, Karachev district of the Bryansk region in the process of drying food wheat grain. (Conclusion) It has been confirmed that the dryer performance is determined not only by the rated capacity but also by the deviation of the current moisture content of grain from the specified values and by the ratio of the amount of heat used for evaporating and heating. The dryer performance at constant initial humidity is determined by its rated performance, the maximum specified difference of grain temperatures, as well as the ratio of the amounts of heat used for evaporating and heating.